Auditor Review of Financial Forecasts: An Analysis of Factors Affecting Reasonableness Judgments. - Danos, Paul; Imhoff, Eugene A. (The Accounting Review, 1982)
Abstract ABSTRACT: This paper reports the results of the experimental stage of a three-stage project which explores many aspects of auditors' involvement in their clients' financial forecasts. The experimental instruments include forecasting factors which were considered important by auditors and which closely paralleled two quite distinguishable corporate settings. Analysis of auditor judgments of the reasonableness of forecasts based on these corporate settings provides evidence which is consistent with the following general conclusions: 1. Models representing individual reasonableness judgments concerning the two cases were relatively well specified 2. The track records of management in forecasting accuracy for net income and sales were the most significant factors in the individual judgment models; and 3. Based on the judgment models employed in the analysis of the experiment, subjects' judgments appeared to be affected by differences in the background information in the two corporate cases.